Strategi Bertahan Dan Bersaing Pada Usaha Mikro Dan Kecil Kedai Kopi Di Masa Pandemi Covid-19 Di Kota Semarang Tahun 2020 - Gavrilla Franzya Handoko; Rogatianus Maryatmo (Universitas Katolik Soegijapranata, Semarang, 2022)
This study aims to analyze the business strategy of micro and small coffee shops in Semarang City, related to the impacts and challenges due to the Covid-19 pandemic. A total of fifty (50) coffee shop MSEs were taken as sample. The analytical tool used in this study is the analysis of Cross Tabulation and Chi Square using SPSS 20 software. The results of the study show that the survival strategy was applied by conducting online promotions to reduce physical promotion costs as well as to penetrate new market targets. Then, the coffee shop also lowered the selling price by giving discounts on the products. The competitive strategy implemented by micro and small coffee shops was to create new products which different from their competitors and provide better services according to government policies by implementing health protocols for coffee shops during the Covid-19 pandemic to increase trust in consumers. Coffee shops also implemented sales through delivery applications such as GoFood and GrabFood to add new target markets.